High-performance eco-concrete beams with calcined montmorillonite, metakaolin pyrolyzed coffee grounds, and hybrid fibers for enhanced bending strength and microstructural refinement - Amani Abdallah Hepautwa; Askwar Hilonga; Register Mrosso; Tusekile Alfredy; Gabriel Mwalusambo; Fina Lesafi; Yusufu Abeid Chande Jande (PLoS ONE, 2026)
This study investigates the flexural performance and microstructural evolution of reinforced concrete beams incorporating calcined montmorillonite (CMMT), metakaolin (MK), pyrolyzed coffee grounds (PCG), and hybrid fibers (steel or banana) as sustainable partial replacements for natural sand and cementitious binders. The replacement levels—12.5% SCM (CMMT or MK) and 15% PCG—were selected based on preliminary optimization trials and evidence from prior studies that identify these ranges as the threshold at which pozzolanic reactivity, workability, and particle packing achieve maximum benefit without compromising matrix integrity. Thirteen mix groups and a control beam were cast and tested under four-point bending, with three replicates per group. Statistical analysis using one-way ANOVA (α = 0.05) confirmed significant differences in peak load, stiffness, ductility, and energy absorption across mixes (p < 0.05). Beams containing CMMT and 1.5% steel fibers achieved the highest flexural capacity, exhibiting a 92–105% increase in ultimate load relative to the control, while mixes with 1.0% banana fibers demonstrated the greatest ductility and post-cracking deformation capacity. Improvements in stiffness (up to 68%) and energy absorption (up to 120%) were closely linked to microstructural refinement observed through XRD and SEM. Quantitative indicators—including a 22–34% reduction in portlandite peak intensity, an increase in amorphous C–S–H content, and visibly compacted interfacial transition zones—corroborated the enhanced matrix densification induced by CMMT and PCG.The combined use of PCG, CMMT, and natural/steel fibers significantly reduced reliance on natural sand and cement while improving structural performance, demonstrating a viable pathway for developing high-performance eco-concretes for structural applications. Although direct durability tests were not conducted, the observed microstructural densification suggests potential improvements in long-term resistance to moisture and chloride ingress, warranting further research.